Assessment of Service Quality of public Physical therapy practice based on SERVQUAL model - Aziz, Sadia; Bhatti, Aziz Ullah; Malik, Tariq; Yusuf, Zeshan (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Quality has become a major determinant in both the industrial and service sectors in order to maximize returns on investments while also contributing significantly to cost reduction. Healthcare, like other service industries, has become a highly contested and rapidly increasing service industry around the world. Objective: The objective of this study was to analyze the functional quality of services provided in the hospital departments of physical therapy in public sector. Methods: The study design was Cross Section Survey. The patients were interviewed through non-probability convenience sampling technique. The respondents were contacted in public hospital in Bahawalpur. The content of questionnaire was validated through literature and SPSS version 16.0 was used for data analysis. The results were extracted by determining patient satisfaction through patient perception and expectation gap, conclusion was drawn, suggestions and recommendations were made. Results: A total of 101 patients, among which 60 patients were male (59 %) and 41 patients were female (40%) were studied. 55 patients (54%) aged 20 to 35 years, 46 patients (45%) aged 31 to 60 years old. Maximum and minimum mean values of expectation are 3.79 in appearance and 2.71 in brochure respectively. The overall quality expectation mean is 3.25. Maximum and minimum mean values of perception are 4.29 in exceed and 1.94 in brochure respectively. The overall quality perception mean is 3.8. Conclusions: The present study concluded that patients’ perception was satisfied with the physiotherapy services rendered to them. The highest level of patients’ perception was the reliability, followed by assurance, responsiveness, accessibility/affordability, tangibility, and the lowest patients ‘perception was the empathy dimension.